New evidence regarding the role of previous disease experiences on people’s knowledge and learning of medicinal plants and biomedical drugs - Santos, Sâmara da Silva; Santoro, Flávia Rosa; Ferreira Júnior, Washington Soares (Ethnobotany Research and Applications, 2023)
Background: What factors influence the knowledge and learning of medicinal plants and biomedical drugs? We investigated this question in a context of intermedicality, exploring previous experiences and the duration of diseases at the individual, family, and community levels. Methods: We conducted our study in a rural community in Northeast Brazil. We use individual semi-structured interviews to gather information on people’s knowledge and learning of medicinal plants and biomedical medications, as well as their prior experiences perceived with diseases at different levels (individual, family, community) and their duration perceived. Results: The knowledge of medicinal plants can be explained mainly by the previous experience of the disease in the community and the family. For medicinal plant learning in one year, only the previous experience in the community is relevant, but it had a negative influence. Regarding the knowledge of biomedical drugs, we observed positive influence of previous experiences in the family and community and negative influence of the diseases’ duration. Finally, none of the predictor variables explained the learning of knowledge of drugs of biomedical origin. Conclusions: The present study suggests important mechanisms that regulate the knowledge and learning of new treatments (medicinal plants and medicines of biomedical origin) in medical systems. Keywords: Evolutionary Ethnobiology, previous experience, risk perception, local medical systems, biomedical system.